Alocação da indústria de fundo de fundos em fundos multimercados no Brasil - Castro, Jonatas Porto de (2017)
This paper’s purpose is to explain the allocations made by fund of funds managers in third-party hedge funds, through a model using public information. Public data such as returns, net inflows, assets under management, ANBIMA classification, administration fee, and others were used as explanatory variables to explain the amount allocated in each hedge fund as a percentage of total AUM allocated in third-party hedge funds. After testing several models, the conclusion is that funds with good 24 months performance, managed by independent firms, with positive net flows in the last 12 months and with high volume of assets under management may have better odds of allocation from fund of fund managers. Thus, variables mentioned above are significant for the estimation of fund of funds allocations in third-party hedge funds. The paper leaves room for further Model developments in order to identify omitted variables. As the information used was the available public data, a second stage is enhancing the Model with qualitative data collected from face-to-face Due Diligences.